ANALISIS KARAKTERISTIK INDIVIDU DAN TINGKAT PENGETAHUAN TENTANG OSTEOARTHRITIS DENGAN STATUS GIZI PADA LANJUT USIA DI DUSUN TAMBAKBAYAN DEPOK KABUPATEN SLEMAN - Chasanah, Siti Uswatun (STIKES Wira Husada Yogyakarta, 2017)
ABSTRACT Elderly need to know about osteoarthritis because it is very important for the elderly, osteoarthritis common in the elderly, by knowing more about the Osteoarthritis disease will greatly assist the elderly in reducing the level of recurrence. The nutritional status of the elderly is the state of a person due to the balance of the substances that enter the body and these substances to meet the needs for growth. This research used analytic observational cross-sectional design with a population of 175 elderly and get 64 samples. This research study analyzes the factors that influence the level of knowledge Osteoarthritis and nutrition status in the elderly. The study population is the elderly as much as 64 respondents. Analysis of the data in this research is the analysis of one variable and analysis two variable with Spearman Rank. To know a descriptive overview of the data collected. Elderly highest age range 66-70 years as many as 28 people (43.8%). Elderly respondents with female sex were 38 (59.4%). Elderly traders work as many as 19 people (29.7%), good knowledge Ostearthritis many as 49 people (76.6), normal nutritional status of as many as 53 people (82.8%), the nutritional status of about 10 people (15.6% ), and nutritional status as 1 (1.6%). Based on Spearman Rank values obtained significancy 0.601 with 0.067 correlation value. In conclusion there was no correlation between the levels of knowledge about Osteoartris in the Elderly with nutritional status in Hamlet Tambak Bayan Depok Sleman, Yogyakarta. Keywords: Knowledge, osteoarthritis, nutritional status